P094 Assessment of intracranial vessels and vascular lesions in rheumatoid arthritis. a detailed transcranial doppler, carotid ultrasound and brain MRI study. (21st February 2018) - Kardos, Z; Oláh, C; Sepsi, M; Sas, A; Kostyál, L; Bhattoa, H; Hodosi, K; Domján, A; Kerekes, G; Tamási, L; Valikovics, A; Bereczki, D; et al.
Abstract : Introduction: Stroke has been associated with rheumatoid arthritis (RA). Vascular physiology should be assessed in the preclinical vascular state. Assessment of intracranial vessels includes transcranial doppler (TCD). TCD performance requires intact temporal acoustic windows (TAW). Failure of TAW (TAWF) is present in 8%–20% of people. This may be due to pathological bone metabolism. Objectives: We assessed RA patients and healthy controls by transcranial Doppler (TCD), carotid ultrasonography and brain MRI. We wished to determine preclinical pathophysiological changes in the cerebral vasculature. Methods: TAWF, temporal bone thickness and texture were determined by ultrasound and CT. BMD and T-scores of multiple bones were determined by DEXA. Several bone biomarkers were assessed by ELISA. Altogether 63 female RA patients and 60 age-matched controls underwent TCD assessment of the medium cerebral (MCA), basilar and vertebral arteries. Pulsatility(PI), resistance(RI) indices and circulatory reserve capacity (CRC) were determined. The presence of carotid plaques and intima-media thickness (cIMT) were also determined. Intracerebral vascular lesions were investigated by brain MRI. RA subsets include MTX- and biologic-treated patients. Results: In RA, the right and left TAW were undetectable in 35% and 53% of patients, respectively. In controls, TAWF was only present in 20% of subjects. Temporal bone was thicker, and texture was more heterogeneous in RA patients was controls (p<0.05). These TAW features were generally more common on the left side. There was close association between TAWF, bone thickness and texture (p<0.05). These TAW parameters all correlated with age, however TAW failure and texture also correlated with serum osteoprotegerin. TAW bone thickness inversely correlated with hip BMD (p<0.05). Conclusions: TAWF, thicker and heterogeneous temporal bones were associated with RA. These features have been associated with bone loss and OPG production. Bone loss seen in RA may result in OPG release and stimulation of bone formation around TAW. This may be the first study to show increased distal MCA and basilar artery occlusion in RA as determined by TCD. RA patients also exert CRC defect. We also confirmed increased carotid plaque formation, increased cIMT. Biologics may beneficially influence some parameters in the intracranial vessels. Disclosure of interest: None declared